Nilai-Nilai Qur'Ani Sebagai Paradigma Perlindungan Perempuan: Solusi Atas Femisida Dan Kekerasan Berbasis Gender - Hamid, Abdul; Firdaus, Slamet; Gumiandari, Septi (Equalita: Jurnal Studi Gender dan Anak, 2024)
The socio-cultural reality today continues to struggle with issues stemming from the marginalization of women, both in domestic and public spheres. Yet, Islamic history unequivocally opposes gender subordination. This study seeks to explore Qur’anic values that are pertinent to the protection of women, with the aim of contributing to the formulation of policies for women's protection and fostering greater societal awareness. The research adopts a descriptive qualitative approach using library research, with references categorized into primary and secondary sources. The findings reveal four key Qur’anic values that serve as safeguards against femicide: (1) Promoting intra-gender synergy as a reflection of human faith, (2) Acknowledging the contributions and roles of women, (3) Ensuring the protection of women's rights, (4) Rejecting the objectification and unjust judgment of women.